Biomolecular Mechanism in Angiogenesis, Wound Healing and its Potential Use as Topical Formulation: A Systematic Review of Antidesma Bunius - Ignatius Erik Dwi Wahyudi; Renni Yuniati; B. Parish Budiono (Eduvest - Journal of Universal Studies, 2026)
Antidesma bunius, commonly known as bignay, is a tropical fruit-bearing plant traditionally used for various medicinal purposes. While its antioxidant, antidiabetic, and anticancer properties have been documented, the specific role of A. bunius in angiogenesis and wound healing remains unclear. This systematic review was conducted following the PRISMA 2020 guidelines. A comprehensive literature search was performed across Scopus, PubMed/MEDLINE, Google Scholar, and Web of Science up to November 2025, using predefined keywords related to Antidesma bunius, angiogenesis, wound healing, and topical formulation. Studies were selected based on inclusion and exclusion criteria, encompassing in vitro, in vivo, and ex vivo original articles. Data were synthesized narratively due to heterogeneity in study designs and outcomes. The review found that A. bunius contains active compounds such as anthocyanins (delphinidin-3-glucoside and cyanidin-3-glucoside), flavonoids (amentoflavone and luteolin-7-galactoside), and phenolic acids. These compounds modulate angiogenesis through multiple pathways, including VEGF/VEGFR2, PI3K/AKT, and HIF-1α signaling. The plant extract demonstrates potential for topical application, with concentrations ranging from 0.01% to 10% w/w showing biological activity. A. bunius shows promising potential as an angiogenic agent for wound healing through its polyphenolic content and multi-target mechanisms; however, standardized clinical trials are needed to establish optimal formulation and therapeutic efficacy.